PENGARUH VARIABEL DEMOGRAFI TERHADAP PERILAKU MENGELUH KONSUMEN PENGGUNA JASA INDUSTRI CENTRAL LAUNDRY DI KOTA DENPASAR - Perdana, I Wayan Fajar Okta; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 4 No 4 (2015), 2015)
The purpose of this study was to determine the influence of demographic on consumer complaining behavior central laundry service user industry in the city of Denpasar. This study used a qualitative research using questionnaires to 100 respondents. Data analysis techniques used in this research is descriptive analysis and chi square. It was found that the characteristics of age, income, education level had a significant relationship with the consumer complaint behavior in service, laundry services, where more than 25 years of age, high income, high education, and consumers who are female tend to submit complaints on services central laundry but did not take any action. Furthermore, the difference between male consumers and women in which consumers are the male sex preferring personal action.
Keywords: Usia, Jenis Kelamin, Tingkat Pendidikan, Tingkat Pendapatan, Perilaku Mengeluh